Thermal quantitative sensory testing as a screening tool for cardiac autonomic neuropathy in patients with diabetes mellitus. Issue 3 (24th February 2022) - Potockova, Veronika; Mala, Sarka; Hoskovcova, Lucie; Capek, Vaclav; Nedelka, Tomas; Riedlbauchova, Lucie; Baumgartner, Daniel; Mensova, Livie; Mazanec, Radim
Abstract: Introduction: Electrophysiological diagnosis of cardiac autonomic neuropathy (CAN) is based on the evaluation of cardiovascular autonomic reflex tests (CARTs). CARTs are relatively time consuming and must be performed under standardized conditions. This study aimed to determine whether thermal quantitative sensory testing (TQST) can be used as a screening tool to identify patients with diabetes at a higher risk of CAN. Methods: Eighty‐five patients with diabetes and 49 healthy controls were included in the study. Neurological examination, CARTs, TQST, biochemical analyses, and neuropathy symptom questionnaires were performed. Results: CAN was diagnosed in 46 patients with diabetes (54%). CAN‐positive patients with diabetes had significantly higher warm detection thresholds (WDT) and significantly lower cold detection thresholds (CDT) in all tested regions (thenar, tibia, and the dorsum of the foot). CDT on the dorsum < 21.8°C in combination with CDT on the tibia < 23.15°C showed the best diagnostic ability in CAN prediction, with 97.4 % specificity, 60.9% sensitivity, 96.6% positive predictive value, and 67.3% negative predictive value. Conclusion: TQST can be used as a screening tool for CAN before CART. Abstract : This study aimed to determine whether thermal quantitative sensory testing (TQST) can be used as a screening tool to identify patients with diabetes at a higher risk of cardiac autonomic neuropathy. Eighty‐five patients with diabetes were included in the study. Cold detection threshold (CDT) on the dorsum of the foot < 21.8°C in combination with CDT on the tibia < 23.15°C showed the best diagnostic ability in CAN prediction, with 97.4% specificity, 60.9% sensitivity, 96.6% positive predictive value, and 67.3% negative predictive value. TQST can be used as a screening tool for CAN before CART in patients with diabetes mellitus.